Paracorporeal Lung Devices: Thinking Outside the Box - Maul, Timothy M.; Nelson, Jennifer S.; Wearden, Peter D. (Frontiers in Pediatrics, 2018)
Extracorporeal Membrane Oxygenation (ECMO) is a resource intensive, life-preserving support system that has seen ever-expanding clinical indications as technology and collective experience has matured. Clinicians caring for patients who develop pulmonary failure secondary to cardiac failure can find themselves in unique situations where traditional ECMO may not be the ideal clinical solution. Existing paracorporeal ventricular assist device (VAD) technology or unique patient physiologies offer the opportunity for thinking “outside the box”. Hybrid ECMO approaches include splicing oxygenators into paracorporeal VAD systems and alternative cannulation strategies to provide a staged approach to transition a patient from ECMO to a VAD. Alternative technologies include the adaptation of ECMO and extracorporeal CO2 removal systems for specific physiologies and pediatric aged patients. This chapter will focus on: 1) hybrid and alternative approaches to extracorporeal support for pulmonary failure, 2) patient selection and, 3) technical considerations of these therapies. By examining the successes and challenges of the relatively select patients treated with these approaches, we hope to spur appropriate research and development to expand the clinical armamentarium of extracorporeal technology.